Pengaruh Pengalaman Persalinan terhadap Tingkat Kepercayaan Diri pada Ibu Hamil Trimester III dalam Menghadapi Persalinan di PMB Rasti Sulastri - Masluroh, Masluroh; Fatimah, Titin (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT According to WHO in 2020, around 287,000 women died during and after pregnancy and childbirth. Sub-Saharan Africa accounts for around 70% of maternal deaths (202,000), while South Asia accounts for around 16% of maternal deaths (47,000). The maternal mortality rate in Indonesia in 2021 is 7,389 mothers. Meanwhile, as many as 1,330 cases or 28.39% of maternal deaths in Indonesia were caused by bleeding. Anxiety that occurs during pregnancy will affect between 15 - 23% of women with an increased negative risk for the mother and child born. Self-confidence can influence the smooth delivery process, affect the health of the fetus, and the health of the pregnant woman herself. To determine the influence of childbirth experience on the level of self-confidence of third trimester pregnant women in facing childbirth. Analytical using cross-sectional method. The sample in this study was all 32 third trimester pregnant women at PMB Rasti Sulastri, West Jakarta in June – July 2024, the sampling technique was total sampling. The frequency distribution of the majority of pregnant women's birth experiences is positive (68.8%), and self-confidence is high (62.5%). There is an influence of childbirth experience on the level of self-confidence of third trimester pregnant women in facing childbirth at PMB Rasti Sulastri (p value 0.002). There is an influence of childbirth experience on the level of self-confidence of pregnant women in the third trimester in facing childbirth. It is hoped that health workers can increase the self-confidence of pregnant women so that pregnant women can have a smooth delivery. Keywords: Childbirth Experience, Self-Confidence, Pregnant Women  ABSTRAK Menurut WHO tahun 2020 menyebutkan bahwa sekitar 287.000 perempuan meninggal selama dan setelah kehamilan dan persalinan. Afrika Sub-Sahara menyumbang sekitar 70% kematian ibu (202.000), sementara Asia Selatan menyumbang sekitar 16 % kematian ibu (47.000). Angka kematian ibu di Indonesia pada tahun 2021 sebesar 7.389 ibu. Adapun, sebanyak 1.330 kasus atau 28,39% kematian ibu di Indonesia disebabkan oleh perdarahan. Kecemasan yang terjadi selama kehamilan akan mepengaruhi antara 15 - 23% wanita dengan peningkatan risiko negatif pada ibu dan anak yang dilahirkan. Kepercayaan diri dapat berpengaruh pada proses kelancaran persalinan, mempengaruhi kesehatan janin, dan kesehatan ibu hamil itu sendiri.  Mengetahui pengaruh pengalaman persalinan terhadap tingkat kepercayaan diri pada ibu hamil trimester III dalam menghadapi persalinan. Analitik dengan menggunakan metode cross-sectional. Sampel dalam penelitian ini adalah seluruh ibu hamil trimester III di PMB Rasti Sulastri Jakarta Barat pada bulan pada bulan Juni – Juli 2024 sebanyak 32 orang, teknik pengambilan sampel adalah total sampling. Distribusi frekuensi pengalaman persalinan ibu hamil mayoritas positif (68,8%), dan kepercayaan diri tinggi (62,5%). Ada pengaruh pengalaman persalinan terhadap tingkat kepercayaan diri pada ibu hamil Trimester III dalam menghadapi persalinan di PMB Rasti Sulastri (p value 0,002). Ada pengaruh pengalaman persalinan terhadap tingkat kepercayaan diri pada ibu hamil Trimester III dalam menghadapi persalinan. Diharapkan tenaga kesehatan dapat meningkatkan kepercayaan diri pada ibu hamil supaya ibu hamil dapat menjalani persalinan dengan lancar. Kata Kunci: Pengalaman, Persalinan, Kepercayaan Diri, Ibu Hamil